Gesture and Language Trajectories in Early Development: An Overview From the Autism Spectrum Disorder Perspective - Ramos-Cabo, Sara; Vulchanov, Valentin; Vulchanova, Mila (Frontiers in Psychology, 2019)
The well documented gesture-language relation in typical communicative development (TD) remains understudied in Autism Spectrum Disorder (ASD). Research on early communication skills shows that gesture production is a strong predictor of language in TD, but little is known about the association between gestures and language in ASD. This review focuses on exploring this relation by addressing two topics: the reliability of gestures as predictor of language competences in ASD, and the types of potential differences (quantitative, qualitative, or both) in the gesture-language trajectory in children on the autism spectrum compared to typically developing children. We find evidence that gesture production is indeed a reliable predictor of early communicative skills, and that both quantitative and qualitative differences have been established in research in the development of verbal and non-verbal communication skills in ASD; with lower gesture rates at the quantitative level, and a trajectory that starts deviating from the TD trajectory only at some point after the first year of life.